HUBUNGAN KOGNITIF DENGAN KEMANDIRIAN ACTIVITY OF DAILY LIVING PADA PASIEN SKIZOFRENIA - Rita Untari; Muhammad Ilham Akbar Maghribi (MOTORIK Jurnal Ilmu Kesehatan, 2020)
Background. Schizophrenia usually has a problem with the function of cognitive function deficits which can affect work activities in daily life. This research aims to determine whether individuals with good cognitive level have more independence in daily activities or vice versa. This research was conducted in RSJ dr. Radjiman Wediodiningrat Lawang with a sample of 50 respondents. To measure the cognitive level used the Allen Cognitive Levels Skills (ACLS) instrument. Then, to measure the independence of Activity of Daily Living (ADL) used Kohlman Evaluating Livings Skills (KELS) instrument. This research aims to determine whether there is a relationship between cognitive level with the independence of daily living activities in schizophrenic patients. Research methods. The design of this research is non experimental quantitative with cross sectional approach and by using Pearson Product Moment correlation data analysis technique through SPPS 16 for windows. Research result. From the result of hypothesis testing Pearson Product Moment Correlation known level of significance (2 tailed) is -0,838 (< 0,05). Conclusion. This research shows that there is relationship between cognitive levels with independence of Activity of Daily Living in schizophrenia patients in RSJ dr. Radjiman Wediodiningrat Lawang. Keywords : cognitive levels, activity of daily living, schizophrenia.